2017
DOI: 10.4103/2277-9175.190981
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Glutathione S-transferases Gene Polymorphisms (GSTM1 and GSTT1) with Ulcerative Colitis and Crohn's Disease in the South of Iran

Abstract: Background:Inflammatory bowel diseases (IBDs), including ulcerative colitis (UC) and Crohn's disease (CD), are chronic inflammatory disorders of the gastrointestinal tract. A combination of environmental factors and interactions with a genetic predisposition are suggested to play an important role in the etiology and pathogenesis of the IBD. Glutathione S-transferases (GSTs) are multifunctional enzymes involved in the cellular oxidative stress handling. Possible associations between GSTs gene polymorphisms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Finally, shared genetic risk loci between rosacea and IBD such as HLA-DRB1*03:01 and butyrophilin-like 2 (BTNL2) could be another explanation for this association. Moreover, an increased prevalence of the glutathione S-transferases theta 1 (GSTT1) null genotype was observed in patients with rosacea and IBD [ 69 , 70 ].…”
Section: The Risk Of Gastrointestinal Disorders In Rosaceamentioning
confidence: 99%
“…Finally, shared genetic risk loci between rosacea and IBD such as HLA-DRB1*03:01 and butyrophilin-like 2 (BTNL2) could be another explanation for this association. Moreover, an increased prevalence of the glutathione S-transferases theta 1 (GSTT1) null genotype was observed in patients with rosacea and IBD [ 69 , 70 ].…”
Section: The Risk Of Gastrointestinal Disorders In Rosaceamentioning
confidence: 99%
“…For example, in one study, GSTM1 -null and GSTP1 Val allele genotypes, were found to increase the risk of nonalcoholic fatty liver in the Iranian population ( 26 ). A significant association was found between GSTM1 null genotype and GSTT1 gene polymorphism in inflammatory bowel diseases ( 29 ). Another study discovered GSTM1 and GSTT1 null genotype are associated with male infertility ( 30 ).…”
Section: Discussionmentioning
confidence: 99%